Lactose intolerance among healthy adults - Achmad Surjono; Teluk Sebodo; Jati Sunarto; Moenginah P. A. (Indonesian Pediatric Society, 1973)
Lactose occurring naturally only in milk, must be hydrolyzed into glucose and galactose by small-intestinal enzyme lactase in order to beutilized. The production and presence of lactase is in the brush-borderof the intestinal epithelial cells and its activity takes place within those cells (Johnson, 1967; Levine and Haft, 1970). The lactase activity is ditributed uniformly throughout the small intestines, except in the duodenum and distal ileum where low levels are found (Auricchio, et al.,1965).